PENGEMBANGAN INSTRUMEN EVALUASI IMPLEMENTASI KURIKULUM PEMBELAJARAN BERBAHASA INGGRIS I-MHERE DI PRODI PENDIDIKAN BIOLOGI FMIPA UNNES: TINJAUAN INDIKATOR DOSEN - Ridlo, Saiful; Supriyanto, Supriyanto (Jurnal Penelitian Pendidikan, 2011)
The problem of this study were (1) how the model construction and evaluation instruments (2) whether the instrument can be used to evaluate the results of the implementation of learning English curriculum in Biological Science Education Program UNNES lecturer in terms of performance indicators. Development of research aims to produce an evaluation instrument and whether the instrument can be used to find English-language classes are conducted in accordance with the expected success criteria I-MHERE program for faculty performance indicators. Methods of model development to take some model development procedure Borg & Gall. Model validation is done through focus group discussions and request a written opinion of an expert. The data were analyzed descriptively and used to produce products in the form of evaluation instruments for use in model evaluation context, input, prosses, and product or the Stufflebeam CIPP. The results component in the form of instruments to evaluate faculty input, the input component of the curriculum, and the components of the curriculum implementation process of learning English I-MHERE Prodi Education in Biology, Mathematics and Natural Sciences, in particular to review the indicators UNNES lecturer. The instrument has been developed to serve the purpose of such instruments are developed until the early trials.